Comparative Electrostatic Force Microscopy of Tetra‐ and Intra‐Molecular G4‐DNA. (4th June 2014) - Livshits, Gideon I.; Ghabboun, Jamal; Borovok, Natalia; Kotlyar, Alexander B.; Porath, Danny
<x xml:space="preserve">Abstract</x> Two forms of G4‐DNA, with parallel and pairwise anti‐parallel strands, are studied using atomic force microscopy. The directionality of the strands affects the molecules' structural properties (different height and length) and their electrical polarizability. Parallel G4‐DNA is twice as polarizable as anti‐parallel G4‐DNA, suggesting it is a better electrical wire for bio‐nanoelectronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>